Pengelolaan Tinggalan Arkeologi di Provinsi Papua - Fairyo, Klementin (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
Management of good and correct of archeology resource for Papua province, having more value especially its relation with special autonomy act execulion has to be more improve the role of society and related institution which means tourism culture Department of Papua province. In the end knowledge about archeology representing important shares from national culture of Indonesia that usefull economically, education, and knowledge and appreciation for human moral vawes.